Implementation of Tolerance Values in Islamic Religious Education at MTs Negeri 5 Sragen - Balqis Tania Prayoga; Dartim Dartim (UNIVERSITAS PAKUAN, 2026)
The purpose of this study is to examine how tolerance values are applied in Islamic Religious Education (PAI) at MTs Negeri 5 Sragen. The study was inspired by the growing phenomenon of intolerance in educational environments that may threaten social harmony and weaken diversity values among students. This research utilized a descriptive qualitative method using a field research design. An Aqidah Akhlak teacher was the main informant for the data collection, which was done through observations, interviews, and recording. Data reduction, data presentation, and conclusion drawing were used to analyze the data. The findings indicate that the implementation of tolerance values was carried out through the integration of tolerance materials in PAI learning, contextual and participatory learning approaches, and the reinforcement of inclusive attitudes through religious and social activities at school. Tolerance values such as tasamuh, ta’awun, husnudzon, and tawadhu’ were implemented through reflective learning activities, peer assessment, and the utilization of social media as an educational medium to strengthen students’ positive behavior and social responsibility. The implementation was supported by the school environment, teachers’ roles, and school policies promoting togetherness and respect for diversity. Nonetheless, disparities in pupils' comprehension and the impact of social media that could spread intolerable narratives were noted as problems. According to the study's findings, Islamic Religious Education uses contextual and participative teaching methods to help students develop tolerance and religious moderation.